Network centrality and core-periphery analysis to clarify the tactics for try in Rugby World Cup 2019 - Sasaki, K.; Yamamoto, T.; Watanabe, I.; Nakayama, M.; Iwabuchi, K.; Katsuta, T.; Kono, I. (American Journal of Sports Science, 2021)
After the first World Cup 1987, rugby undergoes rule revisions aimed at more dynamic games. There have been some analyses of the KPIs (Key Performance Indicators) so far, but not many ones as detailed dynamic network structure of tactics concerned with selected attack and defense areas, plays, and human resources. In current study, the tactics for try in Rugby World Cup 2019 was investigated by network centrality, core-periphery analysis and correspondence analysis. Bootstrap test and ROC analysis were used to validate the data of try contribution structure. The average score of try balance of final 8 teams was "3.94" and that of "not win" teams was "-2.23". We categorized these indices into team performance, and tested Monte Carlo methods with bootstrap hypothesis testing to assess the standardized values. Furthermore, to test the precision of sensitivity and specificity of standardized try balance values, the Area Under the Curve (AUC) of the receiver-operator curve (ROC) analysis was executed. In final 8 stage, the feature of tactics for try in first 20 minutes and last 20 minutes were analyzed. The results suggested the tactics of "attack channel diversity" in first 20 minutes and tactics of "defense and substitute diversity" in last 20 minutes. In addition, network correspondence analysis of the top 4 teams` performance in the tournament yielded interesting results regarding tactics of the attack and defense methods, and of the transition of human resources.